Komparasi Penokohan dari Novel ke Film Seperti Dendam Rindu Harus Dibayar Tuntas - Eriana, Anida; Ekawati, Mursia; Rizal, M. Daniel Fahmi (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The transition of written literary works into cinematic literary works is referred to as ecranization, linguistically the process of transferring from a literary work to film form. The research entitled "Komparasi Penokohan dari Novel ke Film Seperti Dendam Rindu Harus Dibayar Tuntas" is based on the idea that a work can not only be translated, a work can also be translated into other works. This study uses qualitative descriptive methods with an ecranization approach and compares the results of the analysis obtained from the ecranization process. This study aims to find out what are the comparative forms of characterization in novels and films Seperti Dendam Rindu Harus Dibayar Tuntas by Eka Kurniawan with an ekranization approach. The purpose of this study is to obtain a comparative description of characterizations in stories in novels and films Seperti Dendam, Rindu Harus Dibayar Tuntas by Eka Kurniawan based on additions, changes, similarities, and omissions with an approach ekranization. The results of this study obtained 67 data in the form of 7 additions, 10 changes, 13 equations, and 37 omissions from a total of 32 characters contained in the novel.